Strategic Management in Industry 4.0: Digital Transformation in NIKE Inc. Using the Dynamic Capability Approach - Dwi Utami Puterisari (Universitas Teknologi Yogyakarta, 2022)
Today we are in the industrial ecosystem 4.0, which is characterized by various uses of technology such as the Cloud Computerization, the Internet of Things (IoT), Artificial Intelligence (AI) and Big Data which they are part of what is called digital transformation. At this time the company is required to be able to adapt to industry 4.0, especially with digital transformation, in order to the company can survive and still be able to competing with other companies. The research method used in this article is a descriptive research method by using secondary data sources, where secondary data comes from literature studies conducted from the results of searching various articles on the internet. This article discusses how NIKE Inc. carry out digital transformation through dynamic capabilities which consist of sensing, seizing, and transforming processes. Keywords: Industry 4.0, Digital Transformation, Dynamic Capability